(untitled) (Journal of the College of Basic Education, 2022)
Because of when al-Muqtadir was sworn allegiance to God as caliph after the death of his brother al-Muktafi in the year 295 AH, when he was thirteen years old, the line of succession was disturbed, and the Abbasid court witnessed a bloody struggle for power. The Turks overpowered and controlled matters, and their tyranny with power, and one of the effects of this conflict was that he overthrew Al-Muqtadir three times, and finally ended with his killing the Turks after the killing of Al-Muqtadir. And confiscated their property, and arrested Al-Radi Billah Ibn Al-Muqtadir, and tortured his grandmother, Shaghab - Umm Al-Muqtadir - severely, contrary to what she used to treat in the succession of her son, Al-Muqtadir, in terms of benevolence and kindness to him, so Al-Radi spent two years with his grandmother and brothers